Precision of DXA‐Derived Visceral Fat Measurements in a Large Sample of Adults of Varying Body Size. Issue 3 (29th December 2017) - Meredith‐Jones, Kim; Haszard, Jillian; Stanger, Nigel; Taylor, Rachael
Abstract : Objective: The aim of this study was to determine the precision of GE Lunar's CoreScan tool (GE Healthcare, Madison, Wisconsin) for measuring visceral adipose tissue (VAT) in adults of varying body size. Methods: Two consecutive dual‐energy x‐ray absorptiometry (DXA) scans with repositioning were undertaken in 233 participants (110 male, 123 female) aged 18 to 70 years; 38% ( n = 89) had normal weight, 34% ( n = 80) had overweight, and 27% ( n = 64) had obesity. The coefficient of variation (CV), the root‐mean‐square standard deviation (RMS SD), and the corresponding 95% least significant change (LSC) were calculated for VAT, total fat, total lean, bone mineral density, and bone mineral content. Results: VAT precision error in the total group was 28.9% (percent CV), with a RMS SD of 47.1 g. Bland‐Altman plots demonstrated a mean precision bias of 2.4 g (95% CI: −6.2 to 11.0 g), giving an LSC of 130.6 g. BMI subgroup analyses revealed that precision errors (RMS SD) for VAT mass were 32.9 g in the group with normal weight, 33.5 g in the group with overweight, and 51.0 g in the group with obesity. Precision errors (percent CV) for total body fat, lean, and bone were significantly lower, ranging from 0.7% to 2.6%. Conclusions: The precision of DXA VAT mass measurements increase with BMI, and caution should be used with estimates in adults with obesity.